Levels of Elements in Typical Mussels from the Southern Coast of Africa (Namibia, South Africa, Mozambique): Safety Aspect - Pavel Nekhoroshkov (MDPI AG, 2021)
The soft tissues of mussels are often used as the main food source, especially in coastal areas. Neutron Activation Analysis was used to measure the content of 24 macro- and microelements in the soft tissues and 18 elements in the shells of selected sets of mussels of the species Mytilus galloprovincialis. The mussels were collected in 8 polluted and 4 pristine zones, which included Namibia, the west and east coasts of South Africa, and Mozambique. According to factor analysis Co, Ni, Zn, As, Se, Br, I, Sb could have anthropogenic origin. The concentrations of elements such as Cr, As, Se and partly Zn at polluted stations were above the maximum permissible levels for seafood. The concentrations of Sc, V, Cr, Mn, Co, Ni, Sb, Cs, Th, U in shells and soft tissues of the same mussels were at the close levels. Elements such as Al, Cr, Co, As (partly Zn, Se, and I) are considered to be harmful to human health at the levels of mussels consumption of 200 g/week per person and lower in such zones as Swakopmund, East London, Port Shepstone, Richards Bay, Xai-Xai according to calculated risk quotients and target hazard indices.